STRATEGI PEMBELAJARAN MEMBACA PERMULAAN PADA SISWA SEKOLAH DASAR: KAJIAN LITERATUR - Tri Wulandari; Alice Felicia Azaria Hia; Tria Rohana Rahmayani; Nadhifa Nur Rahmah ZD; Ahmad Syarif; Silvina Novianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Beginning reading is the main foundation in developing elementary school students' literacy, determining the success of learning at subsequent levels. This article aims to examine various beginning reading instruction strategies relevant to elementary school students based on literature published within the last five years. This study employs a narrative literature review approach by analyzing sources from accredited national journals and proceedings published in the 2021–2026 period. The findings reveal that beginning reading instruction strategies can be classified into several approaches, including phonics-based strategies, whole language strategies, multisensory strategies, media and technology-based strategies, and cooperative learning strategies. Specific methods extensively reviewed include the spelling method, syllable method (syllabic method), Structural Analytic Synthetic (SAS) method, singing method, as well as the picture and picture and scramble learning models. Supporting factors for strategy implementation include the role of teachers, parental involvement, and the availability of learning media, while inhibiting factors encompass limited facilities, diversity in student abilities, and a lack of teacher training. This study concludes that the selection of beginning reading instruction strategies must be tailored to students' characteristics, the learning context, and the availability of resources to achieve optimal outcomes.